2009
DOI: 10.1021/es9024707
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Perfluoroalkyl Carboxylates and Sulfonates in Drinking Water Utilities and Related Waters from the United States

Abstract: The prevalence and persistence of perfluoroalkyl compounds (PFCs) in environmental and biological systems has been well documented, and a rising number of reports suggest that certain PFCs can result in adverse health effects in mammals. As traditional water sources become increasingly impacted by waste discharge and the demand for planned potable reuse grows, there is recent interest in determining PFC occurrence in drinking water supplies. Here we report monitoring results from drinking water treatment facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(100 citation statements)
references
References 24 publications
6
89
1
1
Order By: Relevance
“…So far, several previous studies have reported the occurrence of PFASs, especially PFOA and PFOS in WWTPs and tap water globally (Ericson et al, 2008;Huset et al, 2008;Jin et al, 2009;Quiñones and Snyder, 2009;Quinete et al, 2009;Arvaniti et al, 2012;Zhang et al, 2013;Schwanz et al, 2016). However, very limited information is available for the various PFASs in DWTPs (Shivakoti et al, 2010;Takagi et al, 2011;Thompson et al, 2011;Eschauzier et al, 2012;Flores et al, 2013).…”
Section: Concentrations and Composition Profiles Of Pfass In Dwtpsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, several previous studies have reported the occurrence of PFASs, especially PFOA and PFOS in WWTPs and tap water globally (Ericson et al, 2008;Huset et al, 2008;Jin et al, 2009;Quiñones and Snyder, 2009;Quinete et al, 2009;Arvaniti et al, 2012;Zhang et al, 2013;Schwanz et al, 2016). However, very limited information is available for the various PFASs in DWTPs (Shivakoti et al, 2010;Takagi et al, 2011;Thompson et al, 2011;Eschauzier et al, 2012;Flores et al, 2013).…”
Section: Concentrations and Composition Profiles Of Pfass In Dwtpsmentioning
confidence: 99%
“…In DWTPs, previous studies showed that coagulation, sand filtration, ozonation, chlorination, and ultraviolet (UV) irradiation are unlikely to be effective for PFASs removal (Quiñones and Snyder, 2009;Eschauzier et al, 2010;Thompson et al, 2011). But granular activated carbon (GAC) and reverse osmosis (RO) can remove PFASs completely when GAC is new (Takagi et al, 2011;Flores et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ponadto wykazano, że pewne ilości PFCs mogą być wypłukiwane z gleby do wód gruntowych i powierzchniowych [42]. W dotychczasowych badaniach wykryto ok. 40 różnych związków perfluorowanych w wodzie pitnej, a ich typowe stężenia mieszczą się w zakresie od pg/dm 3 do ng/dm 3 [2,72,28,54,65]. Odnotowane zawartości na poziomie µg/dm 3 , a nawet mg/dm 3 wynikały natomiast z działań gaśniczych i z sąsiedztwa zakładów produkujących te związki [18,55].…”
Section: Zagrożenia Wynikające Z Obecności Pfcs W śRodowiskuunclassified
“…Nevertheless, its use in some selected consumer application (e.g., semiconductor industry) has been exempted due to the lack of immediate replacement, and industrial effluents from such activities will continue to be the main source of the PFOS entering into the environment [8] Available models predict a continuous PFOS concentration rise in remote areas in the next two decades despite a decline of its concentration in surface ocean water in response to the chemical's phase out [8]. The constant presence of PFOS in surface water presents a potential threat to the security of drinking water, thereby raising extensive interest in controlling its occurrence in the environment [9][10][11][12]. Nanofiltration (NF) is a pressure-driven membrane filtration process that has intermediate characteristics between reverse osmosis and ultrafiltration.…”
Section: Introductionmentioning
confidence: 99%